2006
DOI: 10.1073/pnas.0601287103
|View full text |Cite
|
Sign up to set email alerts
|

A role of the double-stranded RNA-binding protein PACT in mouse ear development and hearing

Abstract: To determine the physiological functions of the mammalian double-stranded RNA-binding protein PACT, the single-copy mouse Pact gene was disrupted and expression of the protein was completely ablated. The most notable phenotypes of the Pact ؊/؊ mouse were reduced size and severe microtia. As a result of the congenital abnormality of both outer and middle ears, these mice were hearing impaired. In situ hybridization revealed that PACT mRNA was expressed in specific regions of all three parts of the ear in adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 31 publications
(18 reference statements)
4
60
1
Order By: Relevance
“…This implication of PACT in endocrine signaling is consistent with its reported role in postnatal anterior pituitary proliferation (25). Our findings add to the repertoire of functions of PACT, which includes the regulation of retinoic-acid-inducible gene 1 expression as part of the antiviral response (26), and ear development and hearing (27).…”
Section: Discussionsupporting
confidence: 74%
“…This implication of PACT in endocrine signaling is consistent with its reported role in postnatal anterior pituitary proliferation (25). Our findings add to the repertoire of functions of PACT, which includes the regulation of retinoic-acid-inducible gene 1 expression as part of the antiviral response (26), and ear development and hearing (27).…”
Section: Discussionsupporting
confidence: 74%
“…We previously established a crucial role of the dsRNA-binding protein PACT in proper development of craniofacial areas, the ears, and hearing (19). Here, we report additional and more pervasive developmental defects of Pact Ϫ/Ϫ mice and trace their origin to the central defect in development of the anterior lobe of the pituitary.…”
Section: Discussionmentioning
confidence: 75%
“…Previously, we generated Pact Ϫ/Ϫ mice and showed that these mice had developmental defects of the craniofacial area and the external/ internal ears, which led to hearing impairment (19). Adult mice had a severe reduction in the size of the outer ear and a large reduction in overall body size versus wild-type (Wt) mice (Fig.…”
Section: Mice Lacking Pact Have Postnatal Growth and Fertility Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR2 also requires TIRAP to bridge MyD88 to the receptor; however it is believed that other MyD88-utilizing TLRs directly recruit MyD88. Recent reports suggest that the requirement for these intermediatory adapters is related to localization of the TLRs to certain domains in the plasma membrane Rowe et al, 2006). The N-terminal domain of MyD88 contains a death domain (DD) that recruits the DDcontaining serine/threonine kinase interleukin-1-associated kinase-4 (IRAK-4).…”
Section: Toll-like Receptorsmentioning
confidence: 99%